Comparative study on Divorce Laws under the law reform (Marriage and Divorce Act 1976) and Islamic family law: transition from divorce based on fault to non-fault ground / Naoko Kuwahara - Naoko, Kuwahara (2006)
This study attempts to specify changes of the Malaysian divorce law for the last twenty years in the modern context. In other words, it analyses lfOUn is for divor , undrr the LRA and the Islamic Family law Act 1984 from th' perspective of distinction of the dissolution of marriage between on fault based ground and the non-foult based ground. It concludes that, from th viewpoint transformation from fault based ground to non-fault based ground of divorce law fault is still matter for the court to grant a decree in the contested case under the LRA. It is, however, hardly presumed that the law is able to rescue the marriage in which the parties have lived apart for such length that the law requires and the attempt to reconcile by a conciliatory body failed. In such case, for the purposes of achieving the object of the divorce law, that is to "enable the empty shell to be destroyed with the maximum fairness and the minimum bitterness, di str s and humiliation", the court should grant a decree where the breakdown of marriage i proved, and should grant an ancillary relief in considering all circumstance including the conduct of the parties and the interests of children. Under the I Jamie Family Law Act 1984, apm'f from the divorce by mutual agr em nt of khul ', fault is principally matter for women. For men, however, fa ult, and furthermore ground, are not necessarily matter as far as law is concerned.